Elite Confederate women in the American Civil War
1 online resource
Keywords: "Elite Confederate Women in the American Civil War is a wide-ranging primary source collection that offers a compelling selection of upper-class, white Confederate women's voices from archives across the South. From the prison diary of Mary Terry to Elizabeth Crozier's eyewitness account of the siege of Knoxville, this volume introduces lesser known voices of the war to show the interconnections between the home front and the front lines, and how the war shaped the lives of women and households across the South. This collection challenges students to engage with the role of first-person narratives in history and to reconsider the roles of southern women in the Civil War. Exploring the themes of slavery, nationalism, secession and occupation, these narratives offer new ways to think about traditional issues in Civil War history and, more broadly, shows the ways in which studies of women and gender can enrich studies of cultures of war. This book is designed for undergraduate and graduate students of both the American Civil War and women's history"--